The evolution of the european regulatory framework for electronic communications - Bauer, Johannes M. (IBEI, 2021)
The paper reviews the historical transformation of the European regulatory framework for electronic communications from the era dominated by state-owned enterprises to the presence of regulated competition. In the course of these developments, the vision of the roles of the public and private sectors in electronic communications changed in expected and unexpected ways. While the period is characterized by a shift toward less direct state intervention, the intensity of regulation has increased in many areas. Most recently, in the wake of the financial crisis, new forms of state intervention can be observed, including public investment in communications infrastructure and public-private partnerships. As a result of the reforms, Europe has been able to achieve major successes but it also suffered unanticipated setbacks compared to other regions. The European Union emerged as the global leader in mobile communications during the 1990s and was able to roll-out first-generation broadband access networks more rapidly than many of its peers. Recently, however, Europe as a whole has not performed as well in deploying next-generation networks and advanced mobile communications services. The paper offers a political-economic explanation for these developments and assesses their effects on the performance of the European electronic communications sector and the economy. From this analysis, the European model emerges as a unique institutional arrangement with peculiar advantages and disadvantages. Once these are recognized, sensible next steps to build the strengths while avoiding the weaknesses of the model can be seen more clearly.